Correlation of Physical Activity, Fast Food Consumption, and Family History With Primary Dysmenorrhea Among Adolescent Girls - Nafisah, Lu'lu (Kesmas Indonesia, 2024)
Primary dysmenorrhea is often experienced by adolescents with different levels of pain. Primary dysmenorrhea affects daily activities, especially in school-age adolescents, and has an impact on their academics and productivity at school. This study aimed to determine the factors associated with the incidence of primary dysmenorrhea in female students at SMP N 2 Karanglewas. This study used a quantitative approach with a cross-sectional research design, with a total sample of 87 respondents at SMP N 2 Karanglewas using a cluster random sampling technique. Data collection was carried out using a questionnaire. Data were analyzed using the chi-square test. There is a relationship between menarche age (p-value = 0.018); physical activity (p-value = 0.008); consumption of fast food (p-value = 0.009); and family history (p-value = 0.000); with primary dysmenorrhea. There is no relationship between the length of menstruation (p-value = 1,000); nutritional status (p-value = 0.556); and stress level (p-value = 0.798). There is a significant relationship between the age of menarche, physical activity, consumption of fast food, and family history with the incidence of primary dysmenorrhea in female students of SMP N 2 Karanglewas. Adolescents with a healthy lifestyle can reduce the risk factors for primary dysmenorrhea.